Santuari e spazi confessionali nell'Italia tardoantica - Luciano, Alessandro (Archaeopress Archaeology, 2021)
The cult of relics led to the transformation of the Late Antique Italian landscape, and of suburban areas in particular. Analysing hypogeal and subdial contexts, this book outlines the evolution of loca sancta, in a process that led the venerated tombs to become first memoriae, then places of worship and finally articulated sanctuaries.